Development Scenarios of the East-West Transport Corridor in the Barents Euro-Arctic Region - Petrova, Tatiana (2023)
The Barents Region is geographically unique, sparsely populated, rich in natural resources, and located far from the main global markets. Transportation, accessibility, and the geographical location of the area were always crucial factors in the area's competitiveness. Transport links economic activities and gives access to resources, markets, and labour. The aim of the research is to establish links between the past, present, and alternative future scenarios in order to provide a holistic picture of the development of the east-west transport corridor. This research focuses on the concept of foresight, which is closely related to strategic planning and development. Foresight is a narrower field of future research that applies futures research techniques to shaping strategies primarily. The research approach is based on a qualitative method. Specific materials such as studies, documents, events, and observations were examined. Research was conducted using secondary data. The data were originally collected and published for two international projects: Northern Axis-Barents Link (NABL) and Barents Region Transport and Logistics (BRTL). These projects were implemented in cooperation with more than 20 partners from four different countries between 2018 and 2022. The lead partner of both above-mentioned projects and the commissioner of this research is the Regional Council of Kainuu. Several theoretical frameworks were used to analyse the data, such as PESTLE analysis, the future cone and triangle, and the general foresight process framework. The main driving forces for change in the transportation sector were identified and divided into six major categories: policy (1), demography and society (2), energy and environment (3), economics (4), finance (5), and technology (6). The research aims to answer three questions. The main bottlenecks of the Northern Axis-Barents Link transport corridor were identified and divided into physical and intangible categories, giving the answer to the first question. The second question ...